EFECTO ANTAGÓNICO DE Zymomonas mobillis spp. FRENTE A Salmonella sp. y Proteus mirabi/is - Maldonado, Claudia M.; Laboratorio de Biotecnología Aplicada Departamento de Microbiología Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2013)
Two methods were employed in this work to study the antagonism of 5 strains of Zymomonas mobilis spp. versus Proteus mirabilis and Salmonel/a sp: the classic method of Ritter and a modified ecometric method. The results obtained showed the antagonic effect of Zymomonas mobilis 560, Zymomonas mobilis mobilis 1 and Zymomonas mobilis pomaceae 1 when inhibit the growth of Proteus mirabilis and Salmonel/a sp; antagonism that was corroborated with the modified ecometric method; in which ICA values lower than 2, alternated with inhibition areas that oscillated between the 3 and 10 mm of diameter.